Synthesis of non-edible biodiesel from crude jatropha oil and used cooking oil - Syazwana, Sapee; Ahmad Fitri, Yusop; Mohammad Nazri, Mohd Jaafar; R., Mamat; Wan Asma, Ibrahim; Hazir, Farouk; Norwazan, Abdul Rahim; lyia Syafira, Ab Razak; Muhammad Syahiran, Abdul Malik; Zhang, B. (EDP Sciences, 2018)
This study focuses on a feasibility study of alternative nonedible crude oil such as jatropha and used cooking oil in biodiesel production. Crude jatropha oil (CJO) and used cooking oil (UCO) were converted to biodiesel using a two-step transesterification process with presents of acid-based and alkaline-based catalysts. Each three biodiesel blends (B5, B15 and B25) have been produced by blended with conventional diesel fuel (CDF). Determination of the fuel properties for each blend including CDF, Jatropha Methyl Ester (JME) and Used Cooking Oil Methyl Ester (UCOME) have been carried out. The average yield for jatropha and used cooking oil biodiesels production was 94.3% and 92% respectively. The increment of the percentage of JME or UCOME in its blends is proportional to fuels physical properties such as density, specific gravity, kinematic viscosity and surface tension, however inversely proportional to fuels calorific value. Based on the results of this study, it is acceptable to conclude that non-edible CJO and UCO are viable alternatives to edible oil as feedstock to renewable fuel in order to reduce the greenhouse gases produced.